2020
DOI: 10.3390/app10217648
|View full text |Cite
|
Sign up to set email alerts
|

Improving School Transition Spaces Microclimate to Make Them Liveable in Warm Climates

Abstract: The so-called urban heat islands (UHI) is a thermal phenomenon characterized by higher air temperatures in the urban area than in rural surroundings. Vernacular passive strategies such as courtyards are proved to be useful to generate specific microclimates, especially in the warmer regions of the Earth. Courtyards increase the porosity of the cities, understanding porosity as building voids. Accordingly, their study will be fundamental in reducing the UHI effect by generating urban cooling microislands. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Studies on UHI mitigation strategies, such as those using green roofs [27,28], cool materials [29], vegetation [30,31], and water sources [32,33], have received a lot of attention recently. Adopting mitigation techniques is crucial for both large urban regions like cities as a whole and smaller localized urban locations like urban canyons [34,35].…”
Section: Urban Heat Island Mitigation Strategiesmentioning
confidence: 99%
“…Studies on UHI mitigation strategies, such as those using green roofs [27,28], cool materials [29], vegetation [30,31], and water sources [32,33], have received a lot of attention recently. Adopting mitigation techniques is crucial for both large urban regions like cities as a whole and smaller localized urban locations like urban canyons [34,35].…”
Section: Urban Heat Island Mitigation Strategiesmentioning
confidence: 99%
“…According to the Köppen classification, the selected cities are defined as Csa, with dry summers with low rainfall and very hot summers. Many case studies were analyzed over an extended period, always exceeding the minimum two-week monitoring period established by previous research [48].…”
Section: Location Climate and Cases Studymentioning
confidence: 99%
“…Recent studies on courtyards and their thermal environment have demonstrated their ability to provide a cool microclimate in the summer [5,6], especially in hot and humid regions [7]. Diz-Mellado et al [8] used thermal comfort modeling to highlight the thermal performance and usability of courtyards in hot climates and demonstrated how courtyards are used to promote thermal comfort in large spaces by casting shadows.…”
Section: Introductionmentioning
confidence: 99%